2014
DOI: 10.2527/jas.2014-7646
|View full text |Cite
|
Sign up to set email alerts
|

Small intestinal growth measures are correlated with feed efficiency in market weight cattle, despite minimal effects of maternal nutrition during early to midgestation1

Abstract: We hypothesized that gestational nutrition would affect calf feed efficiency and small intestinal biology, which would be correlated with feed efficiency. Multiparous beef cows (n = 36) were individually fed 1 of 3 diets from d 45 to 185 of gestation: native grass hay and supplement to meet NRC recommendations (control [CON]), 70% of CON NEm (nutrient restricted [NR]), or a NR diet with a RUP supplement (NR+RUP) to provide similar essential AA as CON. After d 185 of gestation, cows were managed as a single gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 59 publications
5
25
0
3
Order By: Relevance
“…Interestingly, a study by Colnot et al [37] on glucose absorption in the small intestine of neonatal calves demonstrated the primary role of the mucosal growth to trigger the intestinal metabolism of glucose. In another study in calves, Meyer et al [17] demonstrated the relevance of intestinal growth to the variation in feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a study by Colnot et al [37] on glucose absorption in the small intestine of neonatal calves demonstrated the primary role of the mucosal growth to trigger the intestinal metabolism of glucose. In another study in calves, Meyer et al [17] demonstrated the relevance of intestinal growth to the variation in feed efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Montanholi et al [15] observed an increase in the small intestine crypt cellularity in cattle with improved feed efficiency. Such histological and functional evidence is associated with increased metabolic rate of the digestive tract in snakes [16] and also associated with variation in feed efficiency in beef cattle calves [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, another study observed greater liver and empty GIT masses in high RFI compared with low RFI steers (Basarab et al, 2003). In addition, recent data from our lab in feedlot cattle demonstrated a positive relationship between RFI and small intestinal mass and negative relationships between RFI and small intestinal mucosal density and DNA concentration (Meyer et al, 2014). This suggests that more efficient cattle may have smaller intestinal size with a more dense mucosa.…”
Section: Discussionmentioning
confidence: 84%
“…Although nutrient inadequacies generally lead to reduced SI length in several species (Meyer, Hess, Paisley, Du, & Caton, ; Wang, Huo, Shi, Xu, & Hutz, ), progeny from restricted dams and fed the diet without RPF had the longest SI. Rodrigues (), using the same cows and calves in a cow/calf trial until weaning, also reported longer SI in calves from restricted dams.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nutritional restriction during mid to late gestation has long‐term effects on SI length when low lipid diet was used. On the other hand, progeny from restricted cows and fed RPF diet had decreased SI length, a response probably associated to their low DMI, since positive correlation ( r = .32) between intestine length and DMI was found in feedlot steers and heifers (Meyer et al, ). This fact demonstrates the plastic nature of SI, influenced not only by maternal nutrition but also by recent nutritional and environmental stimuli.…”
Section: Discussionmentioning
confidence: 99%